Prognostic Factors at Diagnosis Associated With Damage Accrual in Childhood-Onset Systemic Lupus Erythematosus Patients - Rodríguez-Lozano, Ana Luisa; Rivas-Larrauri, Francisco Eduardo; García-de la Puente, Silvestre; Alcivar-Arteaga, Daniel Alfredo; González-Garay, Alejandro Gabriel (Frontiers in Pediatrics, 2022)
Objectives To associate prognostic factors present at diagnosis with damage accrual in childhood-onset systemic lupus erythematosus (cSLE) patients. Methods We designed a cohort study of eligible children age 16 or younger who fulfilled the 1997 American College of Rheumatology (ACR) classification criteria for SLE. Excluded were those with previous treatment of steroids or immunosuppressants. The diagnosis date was cohort entry. We followed up on all subjects prospectively for at least 2 years. Two experts assessed the disease activity with the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) and Mexican-SLEDAI (MEX-SLEDAI) every 3–6 months. Damage was measured annually, applying Pediatric Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) to their last visit. We analyzed prognostic factors by relative risks (RR) and used logistic regression to construct the clinimetric table. Results Ninety patients with a median age of 11.8 years at diagnosis had a SLEDAI score of 15.5 (2–40) and a MEX-SLEDAI score of 12 (2–29); and of them, forty-eight children (53%) had SDI ≥ 2. The associated variables to damage (SDI ≥ 2) are as follows: neurologic disease RR 9.55 [95% CI 1.411–64.621]; vasculitis RR 2.81 [95% CI 0.991–7.973], and hemolytic anemia RR 2.09 [95% CI 1.280–3.415]. When these three features are present at diagnosis, the probability of damage ascends to 98.97%. Conclusion At diagnosis, we identified neurologic disease, vasculitis, and hemolytic anemia as prognostic factors related to the development of damage in cSLE. Their presence should lead to a closer follow-up to reduce the likelihood of damage development.